The Effectiveness of Alternative IEP Dispute Resolution Practices. (May 2018) - Scanlon, David; Saenz, Lauren; Kelly, Michael P.
Alternative Individualized Education Program (IEP) dispute resolution models should respond to limitations of current options. An experimental IEP dispute resolution program provides parents and schools with an evidence-supported neutral perspective on what is needed for free and appropriate education (FAPE) and least restrictive environment (LRE). Then, instead of being facilitated or directed via a hearing, for example, the parties attempt to resolve their own dispute. Ninety percent of consultations led to a signed IEP. Effectiveness, however, also concerns satisfaction and working relationships between the parties. Follow-up surveys with 36% of parent parties (parent, advocate, attorney), and 33% of school parties (administrator, educator, attorney) were analyzed using concurrent triangulation mixed methods design, including a content coding analysis. Results reveal beliefs by a majority that the process was effective, and working relationships were maintained or strengthened. Lessons for future interactions were learned.